(untitled) (Journal of Hama University, 2022)
Sleep disturbances is a common problem among hospitalized patients and may have an important effect on theirs activities , quality of life, and slow down the recovery. this study was conducted to assess changes in sleep quality of hospitalized patients and to identify the most common causes for disturbed sleep. A descriptive study was conducted on 40 patients who entered Tishreen university between September 2020 and December 2020. Pittsburgh Sleep Questionnaire (PSQI) was used to collect the data from the patients. the results showed that most of patients 95.5% reported poor sleep duality. the noise was the most common cause of disturbed sleep. further studies should conduct about the sleep, enroll sleep quality assessment into the nursing care plan, and modify nursing strategies to promote sleep quality of patients.